(untitled) (International Journal of Engineering and Computer Science, 2016)
Data mining is the process of finding of hidden information from a huge amount of data. Data mining analyzing the data from different source and convert it into meaningful information. In the world of internet there are several online open source resources that are utilized by various academicians. Unfortunately, all the resources that are available in a scattered manner. Because of this factor it required a proper arrangement of data in meaningful information for this we are going to use data mining process which is popularly know as EDM . educational data mining is the emerging topic for research community. educational data mining means to extract the hidden knowledge from large repositories of data with the use of technique and tools. educational data mining develops new methods to discover knowledge from educational database and used for decision making in educational system. The various techniques of data mining like classification. clustering can be applied to bring out hidden knowledge from the educational data. In this paper, we focus on the educational data mining and classification techniques for a specific sector of Education system.